2004
DOI: 10.1111/j.1365-2648.2004.03166.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies used by the relatives of people with obsessive–compulsive disorder

Abstract: Implications for clinical practice to support these relatives are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 20 publications
3
28
0
3
Order By: Relevance
“…Family informal caregivers should not only be considered partners in the patient's treatment process [19,20] and in psychiatric research, [8] but deserve special attention from health care providers for their own psychological morbidity and suffering.…”
Section: Discussionmentioning
confidence: 99%
“…Family informal caregivers should not only be considered partners in the patient's treatment process [19,20] and in psychiatric research, [8] but deserve special attention from health care providers for their own psychological morbidity and suffering.…”
Section: Discussionmentioning
confidence: 99%
“…Allsopp and Verduyn (1990) suggested that some families were split in their responses; one parent may be accommodating whereas the other antagonistic, and some parents may be oscillating in their responses. The latter has been associated with family conflict, which can be stressful for the person with OCD (Van Noppen, Steketee, & Pato, 1997;Stengler-Wenzke, Trosbach, Dietrich & Angermeyer, 2004). Some writers, most notably Guidano and Liotti (1983), theorize that ambivalent parenting might be a risk factor for the development and maintenance of obsessional states.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that many of the OCD patients are completely dependent on their family members. Clinical observations suggest that family members of OCD patients are often involved in patients' rituals: it seems to be a characteristic of patients with OCD to include their relatives in the process of coping with symptoms of the ill- ness [44] . Relatives often become part of the rituals and, even in the patients' absence, take over behavioral rules determined by the compulsions.…”
Section: Compulsions and Qolmentioning
confidence: 99%